Similarities and Differences between Danish and American Physicians’ Religious Characteristics and Clinical Communication: Two Cross-Sectional Surveys - van Randwijk, Christian B. (Religions, 2021)
Many physicians remain reticent to initiate or partake in discussions about their patients’ religious and spiritual needs during the clinical encounter. Reasons for this may be insufficient time, capacity, education or training but may also be a product of variance in physicians’ own religious or spiritual characteristics. The aim of this paper was to compare American and Danish physicians’ religious characteristics, and to explore and compare American and Danish physicians’ attitudes towards, and practices of, integrating religiosity and spirituality in the clinical encounter. We included data from two cross-sectional surveys: an American survey conducted in 2002 (n = 2000) and a Danish survey conducted in 2012 (n = 1485) to test four hypotheses. American physicians were significantly more religious, they more frequently inquired about religious or spiritual issues in the clinical encounter and they found it more appropriate to discuss religious or spiritual issues if the patients brought it up when compared to Danish physicians. A weak to moderate positive correlation between level of religiosity and frequency of inquiring about religious and spiritual issues were found in both populations. The findings are discussed in relation to the clinical importance of ensuring that health care practices stay patient centered. The findings may especially be relevant to consider in increasingly ethnically and culturally diverse contexts.